Cross-Language Pattern Similarity in the Bilateral Fusiform Cortex Is Associated with Reading Proficiency in Second Language. (1st July 2019) - Qu, Jing; Zhang, Lei; Chen, Chuansheng; Xie, Peng; Li, Huiling; Liu, Xiaoyu; Mei, Leilei
Abstract: Previous studies have found that native Chinese speakers recruit the bilateral fusiform gyrus to read English words, in the same manner as they read Chinese words (i.e., the assimilation process). In this study, we quantified the neural pattern similarity between native (L1) and second languages (L2) by using representational similarity analysis (RSA), and examined the modulatory effects of L2 proficiency on cross-language neural pattern similarity (PS) in the bilateral fusiform cortex. Results showed that, for Chinese–English bilinguals, higher reading proficiency in L2 was associated with greater cross-language PS in the left fusiform gyrus, but with lower PS in the right fusiform gyrus. These results suggest that, as L2 proficiency increases, the assimilation process is enhanced in the region for word reading (left fusiform gyrus), but reduced in the region for nonlinguistic processing (right fusiform gyrus). Highlights: Chinese–English bilinguals show similar activations in the bilateral fusiform gyrus when reading Chinese and English words. Pattern similarity between native and second language is quantified by using representational similarity analysis. Proficiency in second language modulates the cross-language pattern similarity in the bilateral fusiform cortex. Increasing L2 proficiency leads to greater pattern similarity in the left fusiform gyrus, but less in the right homologue.